Report of the Agrarian Problem Enquiry Committee - Planning Commission (Planning Commission, 1949)
The Committee held its first meeting in February 1947 and found that questions 1,3 and 4 could be satisfactorily answered only after intensive village enquiries of a certain number of villages in different areas of the State. Conformably to the request of this Committee in this matter, Government was pleased to appoint Mr. S. Subbarama Ayyar, Professor of Economics, Christian College, Tambaram, to make this enquiry with the aid of five Investigators recruited from the staff of the several departments. This enquiry was completed by the end of September 1947. Professor Subbarama Ayyar expects to complete his individual village report and his general report only before February 1948.
Ernakulam
Ernakulam